2016
DOI: 10.1038/ncomms10615
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated SF3B1 mutations affect alternative splicing by promoting alternative branchpoint usage

Abstract: Hotspot mutations in the spliceosome gene SF3B1 are reported in ∼20% of uveal melanomas. SF3B1 is involved in 3′-splice site (3′ss) recognition during RNA splicing; however, the molecular mechanisms of its mutation have remained unclear. Here we show, using RNA-Seq analyses of uveal melanoma, that the SF3B1R625/K666 mutation results in deregulated splicing at a subset of junctions, mostly by the use of alternative 3′ss. Modelling the differential junctions in SF3B1WT and SF3B1R625/K666 cell lines demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
347
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(384 citation statements)
references
References 32 publications
31
347
5
1
Order By: Relevance
“…As observed in murine Sf3b1 -mutant cells, the most common aberrant splicing event in SF3B1 -mutated MDS samples was alternative 3’ splice site (ss) selection (91/134, 67.9%; Figure 4B). The locations of the cryptic 3’ ss in mouse and human cells were both between -15 and -24 nucleotides upstream of the canonical 3′ ss (Figure 4C), similar to recently published reports studying 3’ ss selection in other SF3B1 -mutant cancers (Alsafadi et al, 2016; Darman et al, 2015; DeBoever et al, 2015). Finally, the sequence contexts associated with the cryptic 3’ ss in both the Sf3b1 +/K700E myeloid progenitors (Figure 4D) and SF3B1 -mutant MDS patient samples (Figure 4E) are both characterized by upstream adenosine enrichment and a shorter/weaker polypyrimidine tract (Figure 4F and data not shown), motifs which are in accord with mutant SF3B1 -specific cryptic ss previously reported in chronic lymphocytic leukemia (CLL) and several solid tumor patient samples and cell lines (Alsafadi et al, 2016; Darman et al, 2015).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As observed in murine Sf3b1 -mutant cells, the most common aberrant splicing event in SF3B1 -mutated MDS samples was alternative 3’ splice site (ss) selection (91/134, 67.9%; Figure 4B). The locations of the cryptic 3’ ss in mouse and human cells were both between -15 and -24 nucleotides upstream of the canonical 3′ ss (Figure 4C), similar to recently published reports studying 3’ ss selection in other SF3B1 -mutant cancers (Alsafadi et al, 2016; Darman et al, 2015; DeBoever et al, 2015). Finally, the sequence contexts associated with the cryptic 3’ ss in both the Sf3b1 +/K700E myeloid progenitors (Figure 4D) and SF3B1 -mutant MDS patient samples (Figure 4E) are both characterized by upstream adenosine enrichment and a shorter/weaker polypyrimidine tract (Figure 4F and data not shown), motifs which are in accord with mutant SF3B1 -specific cryptic ss previously reported in chronic lymphocytic leukemia (CLL) and several solid tumor patient samples and cell lines (Alsafadi et al, 2016; Darman et al, 2015).…”
Section: Resultssupporting
confidence: 87%
“…The motif associated with the cryptic 3’ ss is conserved between SF3B1 -mutant human and murine samples and is characterized by an enrichment of adenosines and a short polypyrimidine tract upstream of the cryptic 3’ ss. This splicing abnormality has also been reported in SF3B1 -mutant CLL samples and solid tumors including breast carcinoma and melanoma (Alsafadi et al, 2016; Darman et al, 2015). …”
Section: Discussionsupporting
confidence: 65%
“…We observed a bias in the distance between the canonical to alternative 3’ splice sites associated with SF3B1 mutation. In addition, branchpoints used in SF3B1 WT conditions (Mercer et al, 2015) were found to map at or <10nt from the aberrant 3’ splice site (Figure 1E) and we observed A’s enriched upstream of the aberrant 3’ splice site (Figure S1E), suggesting altered branchpoint usage in the presence of SF3B1 mutation, as recently described (Alsafadi et al, 2016; Darman et al, 2015; DeBoever et al, 2015). Of 4 randomly selected candidate SF3B1 mutation-associated splice variants ( GCC2 , MAP3K7 , TPP2 , ZNF91 ), all were validated as present by quantitative real-time RT-PCR in 10 independent CLL samples, but not in 11 wild-type SF3B1 CLL samples (Table S1, Figure 1F).…”
Section: Resultssupporting
confidence: 85%
“…The critical function of SF3B1 in pre-mRNA splicing leads to the hypothesis that SF3B1 mutations contribute to CLL through the generation of alternatively spliced transcripts. A variety of previous studies have identified splicing alterations associated with mutated SF3B1 in CLL (Alsafadi et al, 2016; Darman et al, 2015; DeBoever et al, 2015; Ferreira et al, 2014; Kesarwani et al, 2016), but the breadth of its functional impact on CLL biology has remained elusive. The study of SF3B1 function has been complicated by difficulties in the genetic manipulation of human B cells and the complex biology associated with altering an essential component of the splicing machinery.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no apparent bias in the sequence motif surrounding splice acceptor sites of cassette exons that were alternatively spliced (Fig. 1c), in contrast to previously observed biases in sequences surrounding alternatively spliced junctions induced by expression of mutant spliceosome proteins U2AF1, SF3B1 and SRSF2 (refs 16, 17, 18, 19, 20, 21, 22, 23, 24, 25). …”
Section: Resultscontrasting
confidence: 76%